Hypolipidemic and Antioxidant Efficacy of Apigenin in Hydrogen Peroxide induced Oxidative Stress in Adult Male Rats (Medico Legal Update, 2021)
This study was conducted to assess the role of apigenin extracted from parsley seeds either in glycosidic(aqueous extract) or aglycone forms (organic solvent extract), comparing to butylated hydroxyl tolouene(BHT)in serum lipid profile and brain tissue peroxidation in H2O2 induced oxidative stress adult male rats.The yield of crude flavonoids from parsley seeds was found to be approximately 2.65% and thin layerchromatography techniques confirmed that apigenin is the main flavonoid with RF similar to that of thestandard apigenin.Experimentally induction of oxidative stress in male rats by 0.75% H2O2 in drinking water for eight weeksshowed a significant alterations in normal serum lipid profile manifested by significant elevation (p